The Hybrid Repair of a Penetrating Ulcer in a Patient With a Bovine Arch; Debranching Followed by Endovascular Stent Placement. (April 2013) - Neragi-Miandoab, Siyamek; Jakobleff, William; Lipsitz, Evan; Michler, Robert E.
Aortic arch disease has conventionally been a subject for open surgical repair, which may require circulatory arrest, accompanied by a long perfusion and extended cross-clamp time. A 2-stage approach utilizing an elephant trunk procedure followed by a descending aortic replacement, or utilizing a frozen elephant trunk with endovascular extension is not well tolerated by multimorbid patients. On the other hand, the endovascular repair of an aortic arch disease is limited by aortic branching. Hybrid repair consists of revascularization of arch vessels followed by endovascular stenting.